MATHEMATICAL MODEL FOR THE RESPONSE OF HPA AXIS APPLYING GOMPERTZ - MAKEHAM DISTRIBUTION IN ASSOCIATION WITH ANALYTIC UNIVALENT FUNCTIONS - et. al., V.G. Shanthi , S. Alamelu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study here is to find the activity of Hypothalamic Pituitary Adrenal axis - HPA which is a major part of human system which controls reaction to stress by finding Cortisol level and the objective is to observe the response of the system over time due to stress by applying the Gompertz - Makeham distribution. Here we develop two functions f 1(z)and f 2(z) by using the class of analytic univalent functions in the open unit disc whose coefficients are considered as Probability density function of the above mentioned distribution, for which the Subordination property, Convex and Star likeness hold. Current study leads us to a real life application by considering the effects on the response of HPA axis to acute stress. The concluded results coincide with the medical findings.